Phytochemical and gas chromatography-mass spectrometry profiling of two plant parts of Sandoricum koetjape (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Saadah S, Tulandi SM, Rohman RA. 2022. Phytochemical and gas chromatography-mass spectrometry profiling of two plant parts of Sandoricum koetjape. Biodiversitas 23: 6199-6207. Sandoricum koetjape has been used in traditional Indonesian medicine for centuries. In Indonesia, the stem and leaves were used to treat helminthiasis, cough, stomachache, diarrhea, bloating, leucorrhoea, colic, and fever. To ascertain the phytochemical constituents of each plant part, and provide a sufficient basis for clinical application, so Gas Chromatography-Mass Spectrometry (GC/MS) analysis of stems and leaves was established. Phytochemical screening showed that stems and leaves contained alkaloids, flavonoids, quinone, triterpenoids, and tannin. Total phenolics in the leaves are higher than in the stem. Saponin and steroids were not detected. The GC/MS analysis indicated that the leaf extract contained more identified compounds (30) than the stem extract (28). Both S. koetjape samples contained 1H-Cycloprop[e]azulen-7-ol. The major compounds of the stem extract of S. koetjape are Fonenol (12.89%), 1H-Cyclopenta[1,3]cyclopropa[1,2]benzene (12.54%), and 1H-Cycloprop[e]azulen-7-ol (11.70%), while the major compounds in leaf methanol extract were 14,15-didehydro-Cyclodecacyclotetradecene (23.71%), 1H-Cycloprop[e]azulen-7-ol (17.04%), and Solanesol (8.34%). The two main components of the variable can account for 50.92% of the total variance, according to Principal Component Analysis (PCA) (PC1 is 21.19% and PC2 is 29.74%). These results indicate that the two components effectively categorize samples with distinct characteristics. The groups were divided based on the type of sample used, namely stem and leaf samples. According to the loading plot, 1H Cyclopenta[1,3]cyclopropa[1,2]benzene and Fonenol are two components that are very effective in categorizing samples based on their type. Both metabolites are higher in the stem than in the leaf. However, the metabolites activities of S. koetjape stem and leaves extracts could be revealed by further studies using in silico and in vitro approaches.